Human Representation on Environmental Speech in Terms of Transitivity Process - Siti Awaliyah Mansyur; Wawan Gunawan; Retty Isnendes (SAGA: Journal of English Language Teaching and Applied Linguistics, 2022)
The role of activists in raising humankind’s awareness regarding environmental or ecological issues or phenomenon has gained so much attention since it is spread and told in many different ways. One of them is taken by sharing the idea through speech and statements that are being spoken before the world leaders, politicians, and any other occasions. This study focuses on the speech of an environmental activist regarding climate change, Greta Thunberg. The analysis was conducted on the transitivity analysis, i.e. the distribution of experiential meaning on the speech that was presented at the United Nations Conference of the Parties on Climate Change, 2018. The result shows: 1) the distribution of material process is the dominant one (41,8%), followed by relational process (19,4%), mental process (17,9%), verbal process (14,9%), behavioral process (3%), and existential process (3%); 2) through the process distribution, human beings seem to have their big roles in causing the climate change, but at the same time they are the ones who can prevent it. Therefore, the speech is regarded as beneficial discourse based on Stibbe’s ecolinguistics standard. This type of discourse has to be promoted in order to raise ecological awareness in society.